Image of Vilnius in Joseph Arthur Gobineau‘s Novel The Pleiades - Bikulčius, Vytautas (Literatūra, 2020)
Using insights from comparative imagology the image of Vilnius in Joseph Arthur Gobineau’s novel The Pleiades (1874) has been analysed in the paper. Presumably, the name of Vilnius was first mentioned by Olympe Chodzko, his Parisian acquaintance, in her short story, its scene is laid in Vilnius. The way Vilnius is imaged depends on context. Where Vilnius is compared to the privileged Saint-Honoré quarter in Paris a tinge of phobia arises unavoidably because Vilnius in no way is comparable to Paris. Likewise is imaged Vilnius by Sophie Tonska, Marquis Candeuil’s sweetheart. Marquis Candeuil selected Vilnius for his residence from seven possible cities accidentally, by drawing lots. That attitude of the protagonist can be related to idiocracy. Where the author writes about Vilnius in the St. Petersburg-Warsaw railroad construction context his philia can be felt. Vilnius is imaged not only in this context, but also through Marquis Candeuil’s thoughts pertaining to the essential problems raised in the novel. Finally, all that reveals that the image of Vilnius in the novel, at first glance so unintentional, actually pertains to the whole system of the novel.
Keywords: Gobineau; Gobinism; Vilnius; philia; phobia; idiocracy